Pelaksanaan Kolaborasi Guru dan Orang Tua dalam Perkembangan Anak di Taman Kanak-Kanak Alam Minangkabau Padang - Resi Novela; Yulsyofriend Yulsyofriend (SELING: Jurnal Program Studi PGRA, 2019)
This study illustrates the collaboration of parents and teachers in the development of children in the Minangkabau Kindergarten, Padang. The research method used is descriptive research with a qualitative approach. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques with data triangulation techniques. The results of the study showed that the collaboration of teachers and parents was very good, namely communication with teachers and parents, contacting via cellphone, contact book, correspondence, and receipt of report cards. In collaboration with teachers and parents there are no significant obstacles because the teacher is always looking for ways to establish collaboration with parents. Teacher and parent collaboration a lot of benefits obtained by the teacher that the teacher can know how the child's development at home, by parents that is knowing the development of children in school, and by the child that is the child will develop properly because what is taught at school will also be applied at home.